REGULATION, SUPERVISION, AND IMPLEMENTATION OF SHARIA PRINCIPLES IN BANKING BY OJK (ANALYSIS OF LEGAL ASPECTS AND CHALLENGES) - Salwatun Aslamia; Ahmed Fatir Sadikin; Muhammad Agil Saputra; Yeni Yulia Kusuma; Tiana Nataza; Rangga Okrio Saputra (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
Banking institutions play an important role in the economic development of the country. Banks are intermediary institutions that cannot be separated from people's lives. Sharia banking is part of the existing banking system in Indonesia which has its own challenges in implementing sharia principles and maintaining its stability. Prior to the establishment of OJK (Financial Services Authority), Bank Indonesia had full authority in supervising the financial services industry, including banking. The Financial Services Authority was established as an answer to problems that arose in the banking sector after the crisis in several national banks. The OJK Law which came into force on November 22, 2011 authorizes OJK to conduct supervision, regulation and investigation in the banking sector in Indonesia. This study discusses the legal aspects of banking regulation and supervision as well as the implementation of sharia principles in OJK sharia banking. The research methods used are legal approaches and literature reviews. The results of the study show that OJK has an integrated regulatory and supervisory function in the entire financial services sector. OJK is considered a superior institution with great authority. OJK also plays a role in regulating and supervising Islamic banking